The Pregnant Mother’s Knowledge Of Gingivitis Disease In The Gestation Toddopuli Makassar - Jauharuddin, Arfiah (Jurnal Ilmiah Amanah Akademika, 2023)
Health is the most crucial aspect of human life. It is essential both physically and spiritually, especially for pregnant women. Regular care is necessary to achieve optimal dental and oral health in toddlers and pregnant women. The occurrence of pregnancy gingivitis in pregnant women is primarily due to an increase in the hormones estrogen and progesterone, leading to the production of more acid in the mouth during pregnancy. However, knowledge of gingivitis is not sufficient to maintain healthy tooth-supporting tissue; dental and oral hygiene measures are equally important. A study was conducted to determine the level of knowledge of pregnant women regarding gingivitis during pregnancy at the Toddopuli Makassar Community Health Center. The research design was descriptive research using a pre-test and post-test design. The study population consisted of pregnant women at Toddopuli Community Health Center, and a purposive sampling technique was used for sampling. The research results showed that most of the respondents had poor knowledge before the counselling (80.0%). However, after the counselling, the majority of respondents' knowledge was classified as good (83.0%).